AKTIVITAS ANTIOKSIDAN BEE BREAD BERDASARKAN ASAL GEOGRAFIS, PELARUT EKSTRAKSI DAN METODE UJI: ARTIKEL REVIEW - Nurfajriya, Syakira; Angelina, Marissa; Kardiman, Reki (Universitas Jambi, 2026)
Bee bread is a naturally fermented product produced by honey bees (Apis mellifera)composed of a mixture of bee salivary gland secretions, pollen, and honey, and is rich in bioactive compounds such as phenolics and flavonoids. The antioxidant activity of bee bread has been reported to vary and is influenced by geographical origin, bee species, extraction solvent, and analytical methods. This review article aims to compare the antioxidant activity of bee bread extracts from various geographic regions of bees based on the results of previous studies. The literature review consists of scientific articles published from 2017 to 2024 obtained from indexed databases such as Google Scholar, PubMed, ScienceDirect, Springer,and Scopus. The type of solvent, antioxidant testing technique, and activity results reported in the form of IC50 or percentage inhibition were all included in the analysis. The results of the study showed that bee bread extracts from Malaysia, especially those extracted using 70%ethanol solvent, were reported to have the highest antioxidant activity. 70% ethanol solvent had the best effectiveness in extracting bioactive compounds. In conclusion, bee bread has the potential as a source of natural antioxidants that can be developed as functional food ingredients and health products.